In-hospital Outcome of Patients Presenting with Acute Anterior STEMI with Complete Right Bundle Branch Block - Sarker, Sudhakar; Chowdhury, Abdul Wadud; Sabah, Khandker Md Nurus; Amin, Md Gaffar; Ali, Mohammad; Saha, Bishnu Pada; Rahman, Md Sajjadur (Cardiovascular Journal, 2018)
Background: Patients with acute anterior ST-segment elevation myocardial infarction (STEMI) and right bundle-branch block (RBBB) have high mortality risk, which may be stratified by early ECG changes. Our objective was to find out and to compare in-hospital outcome of patients presenting with acute anterior STEMI with or without complete RBBB. Methods: This prospective cohort study was conducted in the Department of Cardiology, Dhaka Medical College Hospital, Dhaka, over a period of one year from March 2016 to February 2017. A total of 184 patients were included in this study of which 32 patients were included in group A (acute anterior STEMI with complete RBBB) and 152 patients were included in group B (acute anterior STEMI without any BBB or fascicular block). Results: RBBB was documented in 17.4% (32) of patients with acute anterior STEMI. Acute LVF (50.0% vs. 26.3%, p<0.05), Cardiogenic shock (31.3% vs. 13.2%, p<0.05) and mortality (21.9% vs 7.9%, P<0.05) were more frequently observed in patients with complete RBBB in comparison to patients without any BBB or fascicular block (FB). Among the AMI patients with RBBB, permanent RBBB was associated with a greater incidence of acute LVF (54.2% vs 37.5%, p>0.05), cardiogenic shock (37.5% vs 12.5%, p>0.05) and mortality (25% vs 12.5%, p>0.05). Conclusion: In this study right bundle branch block accompanying acute anterior STEMI was associated with high in-hospital adverse outcomes. Cardiovasc. j. 2018; 11(1): 31-38